My moment : 106 women on fighting for themselves - Chenoweth, Kristin; Najimy, Kathy; Perry, Linda, 1965-; Wright, Chely, 1970-; Blitzer, Lauren (Gallery Books, 2022)
A collection of essays accompanied by beautiful black-and-white photography from a diverse group of women on the moment they realized they were ready to fight for themselves--including Gloria Steinem, Lena Waithe, Joanna Gaines, Brandi Carlile, Beanie Feldstein, Cynthia Erivo, and Billie Jean King, among others.